Clinico-Hematological Pattern of Haematological Malignancies in Patients Referred for Bone Marrow Examination - Hajra Azhar, Hafiz Muhammad Matloob, Nida Khalid, Ayesha Rahman, Javeria Afzal, Najma Qureshi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chromosomal translocation is a common cause among hematological malignancies thus. a different diagnostic and treatment approach is required in these cases. Aim: To determine frequencies and clinic-hematological features of different hematological malignancies among patients. Methodology: It was a descriptive cross sectional study. Patients (n=284) with hematological malignancy were enrolled from total 1080 bone marrow biopsies. Detailed history, clinical examination and hematological parameters were recorded at time of presentation. Bone marrow aspiration and trephine biopsy were done as per the clinical indication. Data was evaluated by using SPSS version 23. Chi-square test was applied with p-value of less than 0.05 was considered significant. Results: The study showed the high percentage of hematological malignancies (24%) were observed among enrolled patients with CML being the commonest cancer among them. Practical Implication: This study established the clinic-hematological correlation and provided study based suggestions for better diagnosis and treatment of hematological malignancies while using bone marrow microscopic examination as an important diagnostic tool. Conclusion: It was concluded that acute leukemias were common in younger age whereas chronic leukemias and lymphoproliferative disorders in more advanced ages. Keywords: Hematological Malignancies, Bone Marrow Examination and Diagnosis.